DIMENSIONS AND EFFECTS OF EMOTIONS IN ORGANIZATIONAL SETTINGS - Andreea ARMEAN (Management Intercultural, 2014)

(untitled)
The emotions and their management in the workplace have become popular topics in the literature as a result of their effects in organizations. With regards to the conceptualization of emotions and their impact within the organizational context, terms such as emotion, affect, and affective state are often used as synonyms by many authors, but there are situations when they have different significance. The meanings associated with these concepts are herein discussed. The affect is present in all the organizational parts, is the root of all its relationships. The emotions influence many organizational dimensions such as decision-making, creativity, teamwork, negotiation, leadership, turnover, and job performance. Another essential construct in this field is emotional labor or the management of emotions. This concept has a special significance in the tertiary sector because it is an important driver of customer satisfaction.